Ação da laserterapia na periodontite experimental induzida em ratos tratados com sinvastatina : estudo bioquímico e radiográfico - Swerts, Andressa Araújo (2014)
The aim of this study was to evaluate the influence of low intensity laser (LLLT) as an adjunct to non-surgical treatment of periodontal disease (PD) experimentally induced in rats treated or not with simvastatin. Seventy-eight rats were divided into 2 groups of 36 animals each. Control group (C) received oral administration of polyethylene glycol 400, whiles sinvastatin group (S) received oral administration of sinvastatin. Both treatments started once a day before the induction of DP, continuing until respective periods of euthanasia. The DP was induced by placing cotton ligature in the supragingival region. After 7 days, the ligature was removed, the animals from both groups were divided into subgroups according to the following local treatments: Scaling and root planning (SRP) and irrigation with saline (R); R followed by application of LLLT (GaAlAs, 660 nm, 4J) (RL). Six animals of each group were euthanized at 7, 15 and 30 days post treatment. Samples of gingival tissues from ligature regions were processed for measurement of oxidative tissue damage by analyzing the content of the tripeptide glutathione (GSH) and malondialdehyde (MDA), the end product of lipoperoxidation by means of high performance liquid chromatography (HPLC), and the occurrence of protein carbonyls content (PCO), estimated by reaction with dinitrophenylhydrazine. The mandibles were sectioned for radiographic analysis. The antioxidant effect of Simvastatin was best observed in the measurement of reduced glutathione (GSH) levels. The malondialdehyde (MDA) does not work as a good marker of oxidative stress in this experimental model, the content of carbonylated protein (PCO) increased significantly (p <0,05) in the control group. In addition, it was observed during radiographic analysis that combination with laser therapy decreases (p <0,01) the bone loss level on the mesial surface of teeth with experimental periodontitis. Restricted to these experimental conditions, the results pointed out to major efficacy of RL and simvastatin concerning to minimize oxidative damage to gingival tissue, and to reducing periodontitisassociated bone loss in rats.